Deaths from all causes in a long-term follow-up study of 11583 deliberate self-harm patients - Hawton, K; Harriss, L; Zahl, D (Cambridge University Press, 2006)
Background. Deliberate self-harm (DSH) may be associated with increased risk of death from a variety of causes, not just suicide. Method. A follow-up study of 11583 DSH patients who presented to a general hospital over a 20-year period was conducted to examine risk of death from a range of causes during a follow-up period of between 3 and 23 years. Deaths were identified through national death registries. Expected numbers of deaths were calculated from national death statistics. Results. The number of deaths (1185, 10.2%) was 2.2 times the expected number, the excess being significantly greater in males than females. Suicides were 17 times more frequent than expected and undetermined causes of death and accidental poisonings 15 times more frequent. Significantly more than expected numbers of deaths from most natural causes were found, including respiratory disease, circulatory, neurological, endocrine, digestive, skin and muskuloskeletal and connective tissue disorders, and symptoms, signs and ill-defined conditions. Deaths due to accidents other than poisoning were more frequent than expected in both genders and homicides more frequent in males. Conclusions. In addition to increased risk of suicide, DSH patients are at increased risk of dying from a wide range of other causes. Possible explanations include lifestyle factors, physical disorders contributing to initial risk of DSH, and social disadvantage. The findings are relevant to clinical management and evaluation of outcome and health-care costs associated with DSH.